Pengaruh Product Ingredients dan Halal Certification terhadap Minat Beli Konsumen pada Produk Mie Udon di Kota Medan: Studi pada Konsumen Produk Mie Udon di Kota Medan (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the influence of Product Ingredients and Halal Certification on Consumer Purchase Intention toward udon products in Medan City. The research background is grounded in the increasing concern of Muslim consumers regarding the clarity of product composition and the legality of halal certification, particularly for foreign food products such as Japanese udon. The study employed a quantitative approach with a causal associative design, involving respondents who had purchased udon products. Primary data were collected through questionnaire distribution, and the analysis was conducted using multiple linear regression. The findings indicate that Product Ingredients have a positive and significant effect on Purchase Intention, with ingredient information emerging as the most dominant indicator because it provides certainty regarding product safety, quality, and halal compliance. Halal Certification was also found to significantly influence Purchase Intention, with the legality of the certifying institution being the most emphasized indicator, while detailed certification information received relatively lower attention. Simultaneously, both variables explained 68% of the variation in purchase intention, with referential intention being the highest indicator, demonstrating consumers’ tendency to recommend the product to others. These results highlight that transparency of ingredients and credible halal certification are crucial factors in shaping consumer purchase intention toward udon products. The study recommends that producers improve clarity of ingredient information, display official halal certification details, and offer product innovations to increase consumers’ exploratory intentions.